Creative activity in the ageing population: Key findings and conclusions - Scarlett, Siobhan; Ward, Mark; Hever, Ann; Kenny, Rose (My University, 2021)
Creative activity participation was high among older adults with over half spending time on creative activities or hobbies at least weekly. Time spent listening to music or radio, and on hobbies or creative activities was lower in older ages but we found higher weekly involvement in reading among this age group. At baseline, we saw higher participation in those with higher educational attainment and the highest income groups in all activities with the exception of going out to plays, films or concerts. The magnitude of involvement, as measured using a creative activity composite score, remained consistent from ages 50 to 74 years but declined more rapidly from age 75 years and older. A number of sociodemographic characteristics were found to be driving factors in participation levels. Higher educational attainment was the strongest predictor of weekly involvement in all activities and positively associated with creative activity scores. Location of residence was not a strong predictor of participation with the exception of going out to films, plays or concerts, where those living in a rural area were less likely to engage than those in an urban area. Participation was also affected by household income. We found that those in the highest household income groups had positive associations with reading, listening to music/radio and spending time on creative activities and hobbies. Furthermore, a positive trend between higher household incomes and creative activity scores was also apparent even while accounting for other sociodemographic characteristics.
PUBLISHED
doi:https://tilda.tcd.ie/publications/research-briefs/CreativeActivity/index.php
Keywords: Ageing